USING THE INTERNET IN HIGH SCHOOL MATHEMATICS - Loong, Esther Yook-Kin (Journal on Mathematics Education, 2014)
Whilst the technological, pedagogical and content knowledge (TPACK) model has been increasingly adopted for understanding teachers’ use of technology, there have been many calls for greater discussion about the constituent constructs, their relationship with one another and the central TPACK. This paper analyses qualitatively the TPACK demonstrated by the teacher of a Year 11class who used web-based simulated contexts and interactive web objects in a Mathematics Studies course. The findings indicate aspects of TPK relating to academic learning time and the transformational mode of the technology were not fully realised in this case study. The implications these has for teacher professional development are discussed.Keywords: Classroom Teaching, Interactive Learning Environments, TPACK, Mathematics Education, Pedagogical Issues. DOI: http://dx.doi.org/10.22342/jme.5.2.1496.108-126